1998
DOI: 10.1046/j.1469-8137.1998.00144.x
|View full text |Cite
|
Sign up to set email alerts
|

Wood decay and phosphorus translocation by the cord‐forming basidiomycete Phanerochaete velutina: the significance of local nutrient supply

Abstract: Mycelial cord systems of Phanerochaete velutina (DC. : Pers.) Parmasto grown from 4 cm$ inocula on a nutrientdepleted non-sterile soil in compartmentalized laboratory microcosms were baited after 13 d of growth with either fresh, non-sterile 4 cm$ wood blocks or control Perspex2 blocks of the same contact area. After 112 d, mature mycelial systems, which were in senescent phase, were subjected to disturbance by supplying a new fresh wood bait diametrically opposite the existing bait and, after 126 d, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 35 publications
2
20
0
2
Order By: Relevance
“…Crucially, we have shown that phosphorus derived from soil in the vicinity of wood newly-colonized by P. velutina exceeds that supplied via translocation from other, previously-colonized, resources by 1-2 orders of magnitude (Wells et al, 1998), suggesting that nutrient translocation driven by demand due to the colonization process itself was unlikely. Why then does phosphorus translocation occur ?…”
Section: mentioning
confidence: 98%
See 3 more Smart Citations
“…Crucially, we have shown that phosphorus derived from soil in the vicinity of wood newly-colonized by P. velutina exceeds that supplied via translocation from other, previously-colonized, resources by 1-2 orders of magnitude (Wells et al, 1998), suggesting that nutrient translocation driven by demand due to the colonization process itself was unlikely. Why then does phosphorus translocation occur ?…”
Section: mentioning
confidence: 98%
“…Secondly, wood decay leads to shrinkage of the bait increasing the likelihood of β-particle scatter away from the scintillation probe window. It is for these reasons that we have previously recommended (Wells & Boddy, 1995 b ;Wells et al, 1997Wells et al, , 1998 that nondestructive counts should only be used to compare like resource units (i.e. those which have been on mycelial systems for the same length of time).…”
Section: mentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have indicated that decomposition of both wood (Merrill & Cowling, 1966 ;Thompson & Rayner, 1982 ;Wells et al, 1998), and needles and leaves (Aber & Melillo, 1980 ;Berg, 1986 ;Cotrufo et al, 1995 ;Cotrufo & Ineson, 1996), can be limited by access to mineral nutrients, particularly nitrogen. The microbial community of the mineral soil also has a high capacity to immobilize mineral nutrients (Stark & Hart, 1997).…”
Section: mentioning
confidence: 99%